Tinjauan Sistematis terhadap Penerapan Etika Bisnis dan Tanggung Jawab Sosial Perusahaan dalam Operasi Multinasional: Perbandingan Perspektif Global dan Lokal - Ardika, Dimas; Padang, Farisah Keke Nola; Rambe, Riswan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research is a systematic review of the application of business ethics and corporate social responsibility (CSR) in multinational companies, by comparing global and local perspectives. lThe method used is a systematic literature review of 18 scientific articles. The results show that multinational companies apply global ethical and CSR standards, but in practice need to be adjusted to local values and norms. These adjustments pose ethical challenges, but also open up opportunities for more meaningful collaboration with communities. The global-local approach is key to maintaining the sustainability and legitimacy of companies in various countries.